SPECIAL AUTONOMY DILEMMA IN THE 1945 CONSTITUTION OF THE REPUBLIC OF INDONESIA - Ahmad Ainun Najib; Indarja Indarja (Syiah Kuala Law Journal, 2023)
As the largest archipelagic country in the world with cultural pluralism in its people, Indonesia, the 1945 Constitution of the Republic of Indonesia has guaranteed the existence of unique or special regional government units. However, in practice, the implementation of special autonomy has been slow in realizing the welfare of the local community. The focus of this research seeks to answer two problems: First, how is the design of special autonomy arrangements in the 1945 Constitution of the Republic of Indonesia? Second, is the implementation of special autonomy in Indonesia following the ideals of regional government regulation in the 1945 Constitution of the Republic of Indonesia? The method used in this research is normative legal research with data collection techniques in library research. The study results reveal that the 1945 Constitution of the Republic of Indonesia has provided space for regions to organize an asymmetrical government. However, in reality, the implementation of special autonomy in Indonesia is not based on the design of regional diversity awareness in the 1945 Constitution of the Republic of Indonesia. In addition, implementing special autonomy in Indonesia still leaves various problems.